KEKUATAN HUKUM PERJANJIAN PINJAM-MEMINJAM UANG DIBAWAH TANGAN (PUTUSAN MA NOMOR 967K/PDT/2016) - TAHI BONAR SINAMBELA (PREMISE LAW JURNAL, 2017)
The case in the Ruling of the Supreme Court No. 967K/PDT/2016 started with an underhanded loan agreement made among Jenda Terkelin with Anthony Sofan and Nurbetty Lingga.The research is done by employing the normative juridical approach with descriptive analysis.The results show that the legal force binding an underhanded deed is stipulated in Article 1875 of the Civil Code, if and underhanded deed is acknowledged by a person to whom it will be used, it binds, and the agreement which is underhandeadly made has binding legal force to the parties who have made it, as regulated in Article 1338 of the Civil Code.Keywords : Agreement, Loan, Underhanded